Characteristics Analysis, Clinical Outcome and Risk Factors for Fungal Peritonitis in Peritoneal Dialysis Patients: A 10-Year Case-Control Study - Li, Rongrong; Zhang, Difei; He, Jingwen; Ou, Jianjun; Zhang, La; Hu, Xiaoxuan; Wu, Jianfeng; Liu, Hui; Peng, Yu; Xu, Yuan; Hou, Haijing; Liu, Xusheng; et al. (Frontiers in Medicine, 2021)
Background: Fungal peritonitis (FP) is a rare but severe complication that can appear in patients receiving peritoneal dialysis (PD). This study aimed to investigate the incidence rate and clinical characteristics of FP, evaluate clinical outcomes between FP and bacterial peritonitis (BP) patients on PD, and especially estimate the risk factors for FP outbreak. Methods: All episodes of FP diagnosed in our hospital from January 1, 2011, to December 31, 2020, were reviewed in this single-center study. FP cases were analyzed and compared with patients diagnosed with BP in a 1:6 ratio matching for case-control study. Patient information, including clinical information, biochemical analysis, and outcomes, was recorded. Univariate and multivariate logistic regression model were used to analyze the risk factors for FP. Results: A total of 15 FP episodes were observed in 15 PD patients, with an FP rate of 0.0071 episodes per patient-year. Seventeen strains of fungi were isolated and identified. Candida was the most common pathogen (15 strains, 88.2%), followed by Aspergillus fumigatus (2 strains, 11.8%). Between the groups, FP group showed a higher rate of HD transfer and catheter removal, and a lower rate of PD resumption in the short-term outcome (all P < 0.01), while no significant difference in the mortality was noted during the whole study period. The multivariate logistic regression analysis showed that longer PD duration (odds ratio [OR] 1.042, 95% confidence interval [CI] 1.012 - 1.073, P < 0.01), higher serum potassium (OR 3.373, 95% CI 1.068 - 10.649, P < 0.05), elevated estimated glomerular filtration rate (eGFR) (OR 1.845, 95% CI 1.151 - 2.955, P < 0.05), reduced serum albumin level (OR 0.820, 95% CI 0.695 - 0.968, P < 0.05) and peritoneal effluent polymorphonuclear (PMN) count (OR 0.940, 95%CI 0.900 - 0.981, P < 0.01) were significantly increased the risk for FP. Conclusion: These results suggested that FP leads to higher rate of catheter removal and HD transfer, and a lower rate of PD resumption than BP, and that additional attention should be paid to hypoalbuminemia, increased serum potassium, long PD duration, and low peritoneal effluent PMN in PD patients.